Model Penerimaan Paul F. Knitter dalam Misi Kristen untuk Keberagaman Agama - Rio Rocky Hermanus; Erlita Silvia; Geovanius Wilson Parassa (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
Pluralism becomes a discourse in religious life, it cannot be denied that it then becomes a space for dialogue between different religions. In dialogue, it should reach the point of accepting differences because at any time there will be no common ground if the debate is about the teaching principles of a religion. The qualitative-descriptive method strengthens this article to see how Christian mission needs to be constructed properly to contribute to Christian religion positioning itself for dialogue with different religions. Starting from this basis, it is necessary to complete it by creating a basis for thinking as well as a basis for dialogue. One effective way is to use the approach offered by Paul Knitter regarding the Acceptance Model. So the result of this article is to create a space for harmonious dialogue that is able to penetrate the boundaries of space that claims mutual truth.